PENGARUH ARUS KAS OPERASI, LABA BERSIH, DAN INVESTMENT OPPORTUNITY SET TERHADAP DIVIDEN KAS (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2022) - Syifa, Layyinatus; Rohman, Fatchur (Accounting Study Program, Faculty of Economics and Business, 2024)
This study aims to explore the relationship between operating cash flow, net income, and investment opportunities on cash dividends through empirical analysis of manufacturing companies listed on the Indonesia Stock Exchange during the 2020-2022 period. Using a quantitative approach, this study involved a population of 241 manufacturing companies listed during the period. Samples were taken using purposive sampling method based on certain criteria, resulting in 55 companies as the final sample. The data was processed using multiple regression techniques supported by SPSS software for numerical analysis. The results revealed that operating cash flow (CFRSER) had a significant negative effect on cash dividends, net income (EPS) had a significant positive impact, while investment opportunities (MBVE) had a significant negative relationship with cash dividends. For future research, it is recommended to use a longer time period to expand the variety of data, as well as include additional variables, such as firm size, profitability, free cash flow, and leverage, to provide a deeper insight into the factors that influence cash dividend policy.